2015
DOI: 10.11603/2415-8798.2015.1.4569
|View full text |Cite
|
Sign up to set email alerts
|

Мелатонін Як Гепатопротектор При Цукровому Діабеті

Abstract: ©Î. Ì. Îëåùóê, ß. ². ²âàíê³â ÄÂÍÇ Òåðíîï³ëüñüêèé äåðaeàâíèé ìåäè÷íèé óí³âåðñèòåò ³ìåí³ ². ß. Ãîðáà÷åâñüêîãî ÌÅËÀÒÎÍ²Í ßÊ ÃÅÏÀÒÎÏÐÎÒÅÊÒÎÐ ÏÐÈ ÖÓÊÐÎÂÎÌÓ Ä²ÀÁÅÒ²ÌÅËÀÒÎÍ²Í ßÊ ÃÅÏÀÒÎÏÐÎÒÅÊÒÎÐ ÏÐÈ ÖÓÊÐÎÂÎÌÓ Ä²À-ÁÅÒ² Äàíà ðîáîòà ì³ñòèòü îãëÿä äàíèõ ë³òåðàòóðè ùîäî ô³ç³î-ëîã³÷íî¿ ðîë³ ìåëàòîí³íó òà çíà÷åííÿ ìåëàòîí³íîâèõ ðåöåï-òîð³â ó ðåàë³çàö³¿ éîãî åôåêò³â. Ïîêàçàíî âïëèâ ìåëàòîí³íó íà ñèíòåç ³íñóë³íó, ïðîô³ëü ãëþêîçè òà éîãî çíà÷åííÿ â ïàòî-ãåíåç³ öóêðîâîãî ä³àáåòó. Òàêîae ðîçãëÿíóòî ìîaeëèâ³ ìåõàí³ç-ìè 䳿 ìåëàòîí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Melatonin also inhibits the formation of peroxynitrite, a toxic oxidants, which formed with the participation of nitric oxide and superoxide anion in terms of pathology [33]. The effect of melatonin on lipid peroxidation, antioxidant enzymes and glutathione content at healthy rats was depicted in our previous work [34]. It was shown that the introduction of the agent promotes the inhibition of lipid peroxidation processes; enhance antioxidant protecting the body and link mitochondrial enzymes chain.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin also inhibits the formation of peroxynitrite, a toxic oxidants, which formed with the participation of nitric oxide and superoxide anion in terms of pathology [33]. The effect of melatonin on lipid peroxidation, antioxidant enzymes and glutathione content at healthy rats was depicted in our previous work [34]. It was shown that the introduction of the agent promotes the inhibition of lipid peroxidation processes; enhance antioxidant protecting the body and link mitochondrial enzymes chain.…”
Section: Discussionmentioning
confidence: 99%